2002
DOI: 10.1007/3-540-45984-7_25
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Generation of Control Programs for Walking Robots Using Genetic Programming

Abstract: Abstract. We present the system SIGEL that combines the simulation and visualization of robots with a Genetic Programming system for the automated evolution of walking. It is designed to automatically generate control programs for arbitrary robots without depending on detailed analytical information of the robots' kinematic structure. Different fitness functions as well as a variety of parameters allow the easy and interactive configuration and adaptation of the evolution process and the simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Busch et al (2002) observed some gaits that cannot found their counterparts in the nature; however, these gaits were slow and not useful for a real robot. This problem is mostly related to a complex state space, in which the search for a solution may be sub-optimal.…”
Section: Related Workmentioning
confidence: 99%
“…Busch et al (2002) observed some gaits that cannot found their counterparts in the nature; however, these gaits were slow and not useful for a real robot. This problem is mostly related to a complex state space, in which the search for a solution may be sub-optimal.…”
Section: Related Workmentioning
confidence: 99%
“…GP is an emerging field in evolutionary computing and machine learning and has already been applied to many tasks, including image analysis [13], object detection [16], regression problems [8] and even control programs for walking robots [3]. GP has been very successful in solving or performing these tasks and "now routinely delivers high-return human-competitive machine intelligence" [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of the study tend to adopt knowledge evolution method, through evolutionary algorithm to automatically generate the appropriate application logic [1] [2][3] [4]. In this paper, using genetic programming (GP) evolution control algorithm for robot path planning.…”
Section: Introductionmentioning
confidence: 99%